Implementasi Etika Bisnis dalam Praktik Usaha Berkelanjutan pada UMKM Mie Jontor Akiw - Umar Mansur; Putri Fadya Azura; Anggie Puji Lestari; Ita Jelita; Galuh Panggraina (Yayasan Literasi Sains Indonesia, 2025)
This study provides an in-depth examination of the implementation of business ethics in sustainable business practices at Mie Jontor AKIW, a local culinary MSME recognized for its strong commitment to moral, social, and environmental values. Employing a qualitative approach with a case study method, the research highlights the application of ethical business principles such as honesty, transparency, accountability, social responsibility, and environmental stewardship. The findings show that Mie Jontor AKIW practices product information transparency through clear labeling and open communication with customers, maintains consistent food quality without the use of harmful preservatives, treats employees fairly by providing decent wages and a safe work environment, and actively engages in community social initiatives and environmental impact reduction efforts, such as waste management and minimizing single-use plastics. These practices have been proven to foster customer loyalty, build a positive reputation, and strengthen business resilience amid competition and market dynamics. Customer perceptions of the enterprise’s integrity and social responsibility are highly positive, indicating that business ethics is not merely a normative obligation but an effective and value-adding sustainability strategy. The study recommends strengthening the integration between business ethics and sustainability objectives as a strategic foundation for developing MSMEs that are more competitive, adaptive, and resilient in the long term.